Zdrada dramatem człowieka i złem moralnym - Drożdż, Alojzy (Śląskie Studia Historyczno-Teologiczne, 2023)
The author presents different types of betrayal. Firstly, the article concerns the betrayal of God, then the betrayal of conscience and other people, and finally the betrayal of one’s ideas. The author describes variant forms of “the negation of faith” in reference to living conditions in communism and accentuates ‘cooperation with evil deed’. First of all the article presents three forms of ‘negation’ and lack of loyalty. Then it mentions “the betrayal in irenism”, “Ajaks’ complex” and “the betrayal for earthly career”. And finally it draws our attention to the “martyrdom inflicted by totalitarianism”. The main thesis revolves around the ethos of people suspended “between heroism and brutality”.